2019
DOI: 10.1111/tpj.14475
|View full text |Cite
|
Sign up to set email alerts
|

Both male and female gametogenesis require a fully functional protein S‐acyl transferase 21 in Arabidopsis thaliana

Abstract: Summary S‐Acylation is a reversible post‐translational lipid modification in which a long chain fatty acid covalently attaches to specific cysteine(s) of proteins via a thioester bond. It enhances the hydrophobicity of proteins, contributes to their membrane association and plays roles in protein trafficking, stability and signalling. A family of Protein S‐Acyl Transferases (PATs) is responsible for this reaction. PATs are multi‐pass transmembrane proteins that possess a catalytic Asp−His−His−Cys cysteine‐rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…AtPAT15 functions are related to β-oxidation of seed storage triacylglycerol during early seedling growth [32]. AtPAT21, another PAT reported recently, participates in both male and female gametogenesis [33]. Further, overexpression of OsPAT15 results in increased branch and seed yield in Brassica napus L. [34].…”
Section: Introductionmentioning
confidence: 97%
“…AtPAT15 functions are related to β-oxidation of seed storage triacylglycerol during early seedling growth [32]. AtPAT21, another PAT reported recently, participates in both male and female gametogenesis [33]. Further, overexpression of OsPAT15 results in increased branch and seed yield in Brassica napus L. [34].…”
Section: Introductionmentioning
confidence: 97%
“…PAT4 was also reported to mediate root hair growth in Arabidopsis [ 42 ]. AtPAT21 , another PAT reported recently, participates in both male and female gametogenesis [ 43 ]. Although ZmPAT7 harbors a conserved DHHC domain that is representative of S-acyltransferases ( Supplementary Figure S2a,b ), and phylogenetic analyses of ZmPAT7 showed that it was highly conserved in monocots, functions of these S-acyltransferase proteins that are close to ZmPAT7 are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). The importance of protein S -acylation has been highlighted in meiotic Arabidopsis , which is involved in the development of male and female sporophyte reproductive structures and associated gametophytes ( Li et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%